The Influence of Product Quality, Lifestyle, and Brand Image on Consumer Purchasing Decisions of VIVO Smartphones - Royhan Bagas Febrianto (Jurnal Ilmu Ekonomi dan Sosial (JIES), 2025)
This study aims to analyze the influence of product quality, lifestyle, and brand image on consumer purchasing decisions for Vivo smartphones in South Tangerang. This study uses a quantitative approach by distributing questionnaires to 160 respondents. Data were analyzed through validity and reliability tests, multiple linear regression, and hypothesis testing (t-test and F-test). The results of the study indicate that product quality has a positive and significant effect on purchasing decisions. Lifestyle has a positive and significant effect on purchasing decisions. Brand image also has a positive and significant effect on purchasing decisions. Simultaneously, all three independent variables have a significant effect on consumer purchasing decisions. The findings of this study confirm that good product quality, a suitable lifestyle, and a strong brand image can increase consumer purchasing decisions for Vivo smartphones.